Taxation strategies for the governance of digital business model—An example of China - Guo, Yi; Zou, Tingting; Shan, Ziwei (Frontiers in Psychology, 2022)
The digital business model emerges as a new business model and gradually penetrates global industries, and countries are putting in place various digital strategies to support their development. As one of the important tools, taxation strategies are highly expected by countries, which not only describe the economic development pattern of a country but also show the digital leadership of a country. Some countries have introduced their own unilateral digital services tax to govern their digital business models, while others have looked more to the global minimum tax, resulting in the current situation of both a unilateral digital services tax and a global minimum tax. However, both of them are of great reference value for the tax governance of digital business models. This paper compares the development history of digital tax strategies, categorizes, and analyzes the design logic of existing digital tax strategies, and takes China, one of the major digital economy countries, as an example to propose China’s digital tax strategies by drawing on international experience. We set an example for the design of digital economy tax strategies for countries around the world so that they can manage digital business models more efficiently.